Pengembangan Peningkatan Keterampilan Berbahasa Jawa yang Santun pada Siswa Kelas IX F SMP Negeri 1 Lasem Semester 1 Tahun Pelajaran 2018/2019 Melalui Model Palu (Pacelathon Bocah Wolu) - Wahyuni, Sri (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2020)
Polite Javanese language skills of students of class IXF Junior High School 1 Lasem Semester 1 Academic Year 2018/2918 are not optimal. Students’ enthusiasm and interest in learning polite Javanese language are still lacking. It is proven from the result of polite Javanese language skills that have not reached the expected target that was 74, 62. It is also proven by the failure to achieve the average mark of polite Javanese language skills of class IXF Junior High School 1 Lasem based on Minimum Completion Criteria (KKM) set by the school that was 80. For the reason, the researcher tried to apply Palu model (Pacelathon Bocah Wolu) in learning activities in an effort to improve polite Javanese language skills. The data sources in this Classroom Action Research are students of class IXF Junior High School 1 Lasem totaling 32 students. This Classroom Action Research aims to find out whether Palu model can improve polite Javanese language skills of students of class IXF Junior High School 1 Lasem or not. This research includes two cycles. Each cycle consists of planning, acting, observing, and reflecting. The data in this research were obtained trough test and non-test instruments. The test instrument is a polite Javanese language skills test. While the non-test instruments include guidelines for observation, interviews, and documentation. The result of the research showed that polite Javanese language skills of class IXF Junior High School 1 Lasem had increased. The result is proven from the average of polite Javanese language skill mark at 79,75 in the first cycle, increasing to 86,18 in the second cycle. With an increase of 6,43. Meanwhile, the completeness of students is 50% in the first cycle, increasing 50% in the second cycle, with a percentage of completeness of 100%. This increase was followed by the changes of students’ attitude who were increasingly enthusiastic, active, brave, and expressive in polite Javanese language skills learning taught by Palu model.